Demonstration of a Polarization-encoding Quantum Key Distribution System - Mantey, Sara T.; Ramos, Mariana F.; Silva, Nuno A.; Pinto, Armando N.; Muga, Nelson J. (Anais do Workshop de Comunicação e Computação Quântica (WQuantum); 2022: Anais do II Workshop de Comunicação e Computação Quântica, 2022)
In this work, a fully functional polarization-encoding quantum key distribution system (QKD) is demonstrated. At the transmitter side, the polarization states are prepared using an algorithm to determine the voltages to be applied on the electronic polarization controller (EPC), to generate up to four polarization states. At the receiver, a second EPC is used to perform the basis alignment. The symbol synchronization is achieved using a reference optical signal that is wavelength division multiplexed with the quantum signal which carries the polarization-encoded qubit. Frame synchronization is achieved at a protocol level. The presented QKD system works at a repetition rate of 500 Hz, with an average quantum bit error rate of 1.35%.